Ekstraksi Kalium dari Abu Kulit Buah Alpukat (Persea Americana Mill) Menggunakan Pelarut Aquades - Mastura, Dewi; Zaini, Halim; Sami, Muhammad (Politeknik Negeri Lhokseumawe, 2024)
One of the primary ingredients in avocado peel skin ash (Persian americana mill) is potassium, which can be utilized as an alkali source while producing soap. Avocado skin has a high potassium potential, which makes it ideal for extraction. Burning the potassium first and then continuing the extraction with distilled water as a solvent are two methods for obtaining potassium. In this investigation, the avocado peel was dried for 24 hours at 110 °C. A crusher is used to crush dried avocado skin into a powder that is then burned in a furnace for 5 hours at 500oC to create avocado skin ash. Variable extraction times are 30 minutes, 60 minutes, and 90 minutes, and the variable mass of avocado skin ash employed in this procedure is 5 g, 7.5 g, and 10 g. The variables for the extraction temperature are 60ºC, 70ºC, 80ºC. The optimum ash mass condition for this method is 7.5 gr, the best extraction temperature is 80oC, the best extraction duration is 90 minutes, and the best potassium concentration is 0.3 N. X-Ray Diffraction (XRD) analysis reveals that the predominant component in avocado skin ash is K2O.